Memories of Konfrontasi and Anti-Malaysia Sentiment in Indonesia - Benedictus Peter Sinarto (Jurnal Empirika, 2020)
Despite Malaysia and Indonesia having similarities in their religious practices, language, and shared ancestry, history has revealed that their relationship constantly fluctuates between peace and hostility. In this paper, we argued that Indonesia’s collective memory of the konfrontasi era has triggered anti-Malaysian sentiment. To elaborate on the answer, first, the constructivism theory regarding identity and interest is used to define the Indonesian sentiment toward Malaysia. Indonesia has a negative sentiment towards Malaysia that distinct from Indonesia's sentiment to other countries. On its negative sentiment toward Malaysia, Indonesia often repeats the slogan of Ganyang Malaysia, which is the infamous slogan from the Konfrontasi era. This paper demonstrated that the ‘false’ collective memory created from the period of Konfrontasi had caused a negative sentiment towards Malaysia. Practically, the sentiment should also be reduced to prevent further escalation with Malaysia since there is already proof that the confrontative attitude toward Malaysia created more damage than the advantage.